Development of in-vitro seed germination assay for Orobanche aegyptiaca Pers. L. to assess the Mustard-Orobanche interaction: Development of in-vitro seed germination assay for Orobanche aegyptiaca Pers. L. to assess the Mustard-Orobanche interaction - REEMA RANI; IBANDALIN MAWLONG; ARUN KUMAR; M S SUJITH KUMAR; V V SINGH; BHAGIRATH RAM; P K RAI (Journal of Oilseeds Research, 2023)
Orobanche aegyptiaca Pers. L. has emerged as a serious constraint to the mustard cultivation in India. Orobanche seed germination requires induction by stimulants present in root exudates of mustard plants. An efficient In-vitro assay is important for understanding the Mustard-Orobanche interactions and evaluation of germplam lines of Indian mustard for Orobanche tolerance. In this study, an efficient and robust method was standardized for Orobanche aegyptiaca seeds germination rate determination under In-vitro conditions. The developed assay is simple and accurate which yields reproducible results for germination bioassays of Orobanche seeds.